2013
DOI: 10.1007/s00299-013-1421-6
|View full text |Cite
|
Sign up to set email alerts
|

Ethylene signaling and regulation in plant growth and stress responses

Abstract: Gaseous phytohormone ethylene affects many aspects of plant growth and development. The ethylene signaling pathway starts when ethylene binds to its receptors. Since the cloning of the first ethylene receptor ETR1 from Arabidopsis, a large number of studies have steadily improved our understanding of the receptors and downstream components in ethylene signal transduction pathway. This article reviews the regulation of ethylene receptors, signal transduction, and the posttranscriptional modulation of downstream… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

4
104
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(112 citation statements)
references
References 137 publications
4
104
0
4
Order By: Relevance
“…He et al (1992) showed increased sensitivity to ethylene in N-and P-deficient roots, which has been further supported in more recent publications (Ma et al, 2003;Kim et al, 2008). Although ethylene's mode of action is not fully understood, a linear signaling pathway has been proposed in Arabidopsis (Shakeel et al, 2013;Wang et al, 2013) EIL indicates Ethylene Insensitive-Like, and ERF indicates Ethylene Response Factor. In the absence of ethylene, the kinase CTR1 phosphorylates EIN2 (which is localized to the endoplasmic reticulum membrane), preventing the cleavage and translocation of the EIN2 C-terminal fragment into the nucleus.…”
supporting
confidence: 53%
See 2 more Smart Citations
“…He et al (1992) showed increased sensitivity to ethylene in N-and P-deficient roots, which has been further supported in more recent publications (Ma et al, 2003;Kim et al, 2008). Although ethylene's mode of action is not fully understood, a linear signaling pathway has been proposed in Arabidopsis (Shakeel et al, 2013;Wang et al, 2013) EIL indicates Ethylene Insensitive-Like, and ERF indicates Ethylene Response Factor. In the absence of ethylene, the kinase CTR1 phosphorylates EIN2 (which is localized to the endoplasmic reticulum membrane), preventing the cleavage and translocation of the EIN2 C-terminal fragment into the nucleus.…”
supporting
confidence: 53%
“…In the presence of ethylene, this is bound to its receptors, and CTR1 is inactivated, resulting in dephosphorylation of EIN2 and its cleavage. The EIN2 C-terminal fragment is then translocated into the nucleus, where it participates in stabilization of the transcription factor EIN3 and downstream gene activation (Shakeel et al, 2013;Wang et al, 2013). EIN3 belongs to a small family of transcription factors that also includes various EIL proteins: EIL1, EIL2, and EIL3 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In this article, we describe investigations of the evolutionary trajectory of this pathway, with particular focus on the role of gene duplication and divergence in that trajectory. Much of our current understanding of ethylene signaling in angiosperms is derived from genetic analyses in Arabidopsis (Stepanova and Alonso, 2009;Yoo et al, 2009;Wang et al, 2013). Essentially, ethylene binds to membrane-spanning ethylene receptors (e.g.…”
mentioning
confidence: 99%
“…The ethylene receptor family has been divided into two subfamilies (type I and II) on the basis of structural similarities of Arabidopsis ethylene receptors (Gamble et al 1998;Moussatche and Klee 2004). Several studies have demonstrated that ethylene receptors display spatial and temporal regulation at the transcriptional level following perception of internal (developmental) and external (environmental) stimuli, such as ripening, senescence, wounding, dehydration, and pathogen infection (Ciardi and Klee 2001;Wang et al 2013). Ethylene receptors have been extensively studied in model plant, interestingly, analyses of their expression patterns have indicated that their regulation is complex and varies in relation to tissue, organ type and stress (Grefen et al 2008;O'Malley et al 2005).…”
mentioning
confidence: 99%